(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of overweight and obesity and analyze the association between nutritional status and quality of life among inpatients undergoing traditional medicine treatment. Subject and method: A cross-sectional study was conducted on 386 inpatients at three hospitals in Ho Chi Minh city from April 2024 to February 2025. Nutritional status was classified using BMI based on the Asian BMI criteria. Quality of life was assessed using the EQ-5D-5L instrument. Results: The prevalence of overweight and obesity was 46.4%. No statistically significant associations were found between overweight and obesity and gender, age, occupation, or education. Frequent consumption of fatty foods increased the risk of overweight and obesity (OR = 2.78; p < 0.05). The overweight and obesity group had higher levels of hemoglobin and lymphocytes (p < 0.001). Although EQ-VAS scores were lower in the overweight and obesity group than in the non-overweight and obesity group, the difference was not statistically significant (p = 0.189). Conclusion: Overweight and obesity are common among traditional medicine inpatients and are likely associated with reduced quality of life. Early nutritional assessment and intervention should be integrated into comprehensive inpatient care in traditional medicine settings.